1999
DOI: 10.1029/1999wr900173
|View full text |Cite
|
Sign up to set email alerts
|

Assessing rooting depths of an austrian pine stand by inverse modeling soil water content maps

Abstract: Abstract. Rooting depths in a forested stand (0.11 ha) were estimated indirectly by inverse modeling maps of soil water contents from time domain reflectometry (TDR) measurements at 150 points. These maps were described with a calibrated onedimensional soil water flow model, with specific values for the rooting depth, van Genuchten's [1980] a parameter, and throughfall fraction at each point. At about one third of the 150 points, modeled rooting depths did not fall within the a priori likely range of rooting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 23 publications
6
26
0
Order By: Relevance
“…The gentle slope of the K functions from the Swartland was consistent with the low clay content (< 22 %) and the presence of saprolite rock in the C horizon. Similar observations of clay soils were made by Freankel (2008) and Nhlabatsi (2011). Given the poor drainage properties of Tukulu and Sepane, it was proposed that a zero drainage flux be assigned at the bottom of these soil profiles for soil water balance studies (Hensley et al, 2000).…”
Section: Comparison Of In Situ and Predicted K Functionsupporting
confidence: 52%
See 2 more Smart Citations
“…The gentle slope of the K functions from the Swartland was consistent with the low clay content (< 22 %) and the presence of saprolite rock in the C horizon. Similar observations of clay soils were made by Freankel (2008) and Nhlabatsi (2011). Given the poor drainage properties of Tukulu and Sepane, it was proposed that a zero drainage flux be assigned at the bottom of these soil profiles for soil water balance studies (Hensley et al, 2000).…”
Section: Comparison Of In Situ and Predicted K Functionsupporting
confidence: 52%
“…The hydraulic parameters are usually based on the SWRC, because it is easily measured and can be estimated using a parameter optimisation technique (Kool et al, 1987;Hopmans and Simunek, 1999). Several studies applied inverse modelling and parameter estimation of hydraulic functions directly from in situ drainage transient experiments (Dane and Hruska, 1983;Romano, 1993;Zijilstra and Dane, 1996;Musters and Bouten, 1999;Dikinya, 2005). Agreement between in situ and predicted hydraulic functions was generally satisfactory, even though the K function was highly variable.…”
Section: S S W Mavimbela and L D Van Rensburg: Estimating Hydraumentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that no unique vegetation parameter can be obtained by matching observed and simulated θ and the vegetation parameters are falsely linked parameters and not sets of partially linked parameters since ΔE > 10% and ΔINT > 10%. These finding are similar to Hupet et al (2002;2003), , Musters and Bouten (1999;2000) that found that the root water uptake parameters are not sensitive enough to be calibrated against θ.…”
Section: Feasibility Testsupporting
confidence: 77%
“…In the present case study we assume the hydraulic parameters are known and we want to know whether accurate groundwater recharge could be determined by optimising the vegetation parameters against θ. The root water uptake parameters are assumed to be known, since Hupet et al (2002;2003), , Musters and Bouten (1999;2000) showed that the root water uptake parameters are not sensitive enough to be optimised against θ. In this case study the vegetation parameters consists of 3 parameters: 2 interception parameters and 1 crop factor parameter.…”
Section: Introductionmentioning
confidence: 99%